Variable Power Supply (variable output) / Wan Imran Fitri Wan Ab Malek and Mohd Zulkepri Ismail - Wan Ab Malek, Wan Imran Fitri; Ismail, Mohd Zulkepri (2005)
This project - Variable Power Supply - is designed to get a voltage in range that we had set first. Our output are consists of two variable output that was variable DC voltage and variable AC voltage In this project, the important thing is how to make the value of output be variable. This project will be giving the value of voltage that we need to use. From this project it can make us easier to use any device in our live that use voltage to operate that thing.